Growth, Yield and Water Economy in Egg Plant (Solanum melongena L.) as Influenced by Drip Irrigation and Biofertilizers - Jadhav, K V; Mehta, H M; Lakkad, L V (Annals of Arid Zone, 2016)
Growth parameters, yield attributes. total fruit yield and water-use efficiency (WUE) increased significantly with irrigation scheduling through drip at 0.8 CPE compared to check basin system. Drip irrigation at 0.8 CPE resulted in 28.4% saving in water, 12.3% higher total fruit yield and two fold higher WUE over check basin irrigation system. Fertilizer application of 100 kg N ha-1 through urea. 1.43 t ha-1 dry azolla (equivalent to 50 kg N ha-1 and inoculation with Azotobactr. ABA-1. were found significantly superior to their lower levels in respect of growth parameters, yield attributes. total fruit yield and WUE of egg plant.